Wide-field plate archives stored in the Ukrainian observatories - Tsvetkova, K.P.; Tsvetkov, M.K.; Sergeeva, T.P.; Sergeev, A.V. (Кинематика и физика небесных тел, 2009)
The latest version of the Wide-Field Plate Database Catalogue of Wide-Field Plate Archives (April 2008) contains 43 archives stored at some Ukrainian observatories, namely, at the Main Astronomical Observatory of the National Academy of Sciences of Ukraine (Golosiiv, Kyiv), at the Crimean Astrophysical Observatory (Nauchnyi and Simeiz), at the Kyiv, L’viv, and Odesa University Observatories, and at the Mykolaiv Observatory. About 126 000 plates were obtained from 1898 to 2005. Последняя версия каталога архивов широкоугольных пластинок (Catalogue of Wide-Field Plate Archives, April 2008) содержит 43 архива, хранящихся в нескольких обсерваториях Украины: в Главной астрономической обсерватории НАН Украины (Голосиив, Киев), в Крымской астрофизической обсерватории (Научный и Симеиз), в обсерваториях Киевского, Львовского и Одесского университетов и в Николаевской обсерватории. Около 126 000 пластинок было получено в период с 1898 по 2005 гг. Остання версія каталогу архівів ширококутних платівок (Catalogue of Wide-Field Plate Archives, April 2008) містить 43 архіви, що зберігаються в декількох обсерваторіях України: у Головній астрономічній обсерваторії НАН України (Голосіїв, Київ), Кримській астрофізичній обсерваторії (Научний і Сімеїз), в обсерваторіях Київського, Львівського й Одеського університетів і в Миколаївській обсерваторії. Близько 126000 платівок отримано з 1898 по 2005 рр.